Análisis del impacto ambiental de los productos químicos utilizados en la agricultura del Ecuador - Alava Mora, Jean Pierre (2021)
Agrochemicals are chemical substances or mixtures of substances, intended to prevent, destroy, control or interrupt the biological cycle of any plague, diseases and weeds; Its use in agriculture dates from the 20th and 19th centuries. However, over time it has been shown that their indiscriminate use represents an environmental problem with a serious impact. In this sense, the present work prior to qualification is intended to analyze the environmental impact of chemical products used in agriculture in Ecuador, based on a review of bibliographic sources. For their part, pesticides, especially organophosphates, organochlorines and carbamates (agrochemicals with the greatest environmental impact) and chemical fertilizers have caused eutrophication, water toxicity, groundwater pollution, air pollution, soil and ecosystem degradation, biological imbalances. and reduction of biodiversity; Said environmental contamination is fundamentally caused by direct applications in agricultural crops, inadequate washing of container tanks, leaks in storage tanks and waste discharged and disposed of on the ground, accidental spills, and inappropriate use of them by the population. Therefore, it is necessary to embrace good agricultural practices such as: (1) selecting the specific product for the pest to be controlled, respecting the technical justification of both the professional in charge and the label; (2) the personnel in charge of handling and applying pesticides must use personal protection elements; (3) respect the application rate; (4) respect the times of re-entry to the property; (5) management and handling of containers; (6) proper storage and (7) waste control.